2018
DOI: 10.1371/journal.pone.0198663
|View full text |Cite
|
Sign up to set email alerts
|

Win for your kin: Neural responses to personal and vicarious rewards when mothers win for their adolescent children

Abstract: Mother-child relationships change considerably in adolescence, but it is not yet understood how mothers experience vicarious rewards for their adolescent children. In the current study, we investigated neural responses of twenty mothers winning and losing money for their best friend and for their adolescent child in a gambling task. During the task, functional neuroimaging data were acquired. We examined the activation patterns when playing for or winning for self, adolescent children and friends in four a-pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
3
12
0
Order By: Relevance
“…We found that higher ventral striatum activity related to more closeness with the concurrent best friend in participants with unstable best friendships. These results are in line with previous findings suggesting that the closeness of a relationship predicts striatum responses to vicarious rewards 8 , 35 , 36 . The findings showing that closeness did not explain individual variation in stable best friend relationships could be due to less variation in closeness experienced in stable best friendship (i.e., mostly high).…”
Section: Discussionsupporting
confidence: 93%
“…We found that higher ventral striatum activity related to more closeness with the concurrent best friend in participants with unstable best friendships. These results are in line with previous findings suggesting that the closeness of a relationship predicts striatum responses to vicarious rewards 8 , 35 , 36 . The findings showing that closeness did not explain individual variation in stable best friend relationships could be due to less variation in closeness experienced in stable best friendship (i.e., mostly high).…”
Section: Discussionsupporting
confidence: 93%
“…In other words, these regions seemed to process vicarious rewards for fathers even in conditions where the participants themselves won nothing. These regions correspond to earlier findings (Schreuders, Klapwijk, Will, & Güroğlu, 2018;Spaans, Burke, et al, 2018a) during donation and vicarious reward tasks and are known to belong to a social brain network (Blakemore, 2008;Frith, 2007;Kanske, Böckler, Trautwein, & Singer, 2015). Interestingly, prior research by Mitchell, Macrae, and Banaji (2006) and subsequent meta-analyses (Denny, Kober, Wager, & Ochsner, 2012) revealed that the medial PFC and precuneus are important regions for differentiating between self and distant and close others.…”
Section: Discussionsupporting
confidence: 86%
“…others (Braams & Crone, 2017;Morelli et al, 2015;Spaans, Burke, et al, 2018a). No such effect was found when winning for strangers.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Correspondingly, activation in these areas has also been found when parents make judgments about traits of their offspring ( Laurita et al. , 2019 ) or when mothers receive rewards for their offspring ( Spaans et al. , 2018 ).…”
Section: Discussionmentioning
confidence: 99%